Unusual Congenital Development of Hoof- and Tail-Like Structure in the Buccal Mucosa of a Buffalo Calf: A Rare Case Report - Prarthana, R.; Kumar, Rohit; Purushotham, R.V.; Ramu, Deva; Gopinathan, Aswathy; Kamalesh, K.S.; Singh, Bhanu Pratap; Singh, Kiranjeet; Kumar, Pawan (Journal of Buffalo Science, 2025)
A rare congenital anomaly was observed in a neonatal buffalo calf presenting with unusual tissue growth resembling hoof and tail-like structures within the oral mucosa. This case is the first of its kind reported in buffalo calves and contributes to the limited literature on oral anomalies in large animals. The buccal space's limited size and distribution of adipose tissue make it an anatomically significant location. Clinical and histopathological evaluations were conducted to characterize the nature of the growth because of the variety of tissues present. A unilateral (right side) buccal space tissue (horn and tail) growth and its surgical management, along with prognosis, are discussed in this report.